Variability of Autumn Tropical Pacific Yellowfin Tuna Tied to the Spring North Atlantic Tripole - Gongjun Zhang; Jianping Li (Geophysical Research Letters)
Abstract Climate change affects the spatial distribution and abundance of yellowfin tuna (Thunnus albacares, YFT) in the tropical Pacific, yet the mechanisms linking remote climate modes to YFT dynamics remain unclear. This study finds that the variability of autumn tropical Pacific YFT is tied to the spring sea surface temperature anomalies (SSTAs) of the North Atlantic Tripole (NAT), mediated by the Victoria Mode (VM), the second dominant mode of North Pacific SSTAs variability. The result shows that the spring NAT is significantly positive correlated with the subsequent autumn tropical Pacific YFT catch per unit effort (CPUE). The spring NAT triggers eastward‐propagating Rossby waves, inducing VM‐like SSTAs in the North Pacific. These anomalies modify YFT habitat conditions in the tropical Pacific through coupled oceanic‐atmospheric bridge (COAB) mechanism, ultimately affecting autumn CPUE. This study unveils a teleconnection‐driven mechanism influencing tropical Pacific YFT CPUE, with important implications for fisheries management and forecasting.